High‐efficient surface tailoring via reverse atom transfer radical polymerization and reversible addition‐fragmentation chain‐transfer polymerization in an aqueous system initiated by a monocenter redox pair. Issue 10 (4th February 2022) - Yang, Haicun; Cai, Shuipi; Jiang, Yu; Cao, Zheng; Ma, Wenzhong; Gong, Fanghong; Tao, Guoliang; Liu, Chunlin
Abstract: The commonly used multi‐center initiation methods always lead to the formation of quantities of homopolymer in the surface tailoring based on reverse atom transfer radical polymerization (ATRP) and reversible addition‐fragmentation chain‐transfer (RAFT) polymerization. In this study, a monocenter redox pair constructed of silica bearing tert‐butyl hydroperoxide groups and ascorbic acid (SiO2 ‐TBHP/AsAc) was applied to substitute the commonly used initiation method of R‐supported RAFT grafting polymerization. All the propagating radicals were restricted on the surface of solid particles during the whole procedure theoretically, resulting in a higher grafting efficiency of 95.1% combined with the "controllable" feature at 10 h. This redox pair was also used to initiate the reverse ATRP in miniemulsion successfully with a grafting efficiency of 86.3% at 10 h. The grafting efficiency obtained under this monocenter initiation method was significantly higher than that of the frequently reported surface modification by reverse ATRP and RAFT polymerization. In addition, the high‐efficient surface tailoring was traced and confirmed by nuclear magnetic resonance, Fourier transform infrared, X‐ray photoelectron spectroscopy, thermogravimetric analysis, transmission electron microscopy, and other analysis tests. The advantage of this monocenter redox pair will open a new avenue for the potential "high‐efficient" surface tailoring of various materials. Abstract :